Management of Ahiputana (Diaper Rash) though Triphala Khadir Yog (TKY) Avachoornan (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda is an ancient medical system that addresses both the state of Swasthya, or optimal human health, and a broad range of illnesses and associated therapies. One of the most frequent issues in pediatric OPD is diaper rash. According to Ashang Hridaya, Maloplep (contained faeces) and Sweda (sweat/perspiration) both causes Kandu (irritability), Daha (burning sensation) and Tamra Varna (redness), Strava (discharge), Vrana (wound formation around the perianal region), Pidika (papulovesicular lesion) around the Guda area (napkin area). In Ahiputana there is Pitta, Kapha and Rakta Dosha Prakop (increase). In present case report, a 11-month-old female baby patient presented in Balrog OPD 13 of Sane Guruji Rugnalaya, Hadapsar, Pune, with complaints of loose motion episodes, itching and redness associated with discharge and burning sensation for 3 days and was treated with external application of Triphala Khadir Yoga. After complete treatment of 10 days, there was complete remission in the symptoms and there is no recurrence till date. From the current case report, it can be inferred that Ahiputana (diaper rash) can be successfully treated with the appropriate Ayurveda medications.